Experimental Study on a Novel Foaming Formula for CO2 Foam Flooding - Xu, X.; Saeedi, Ali; Liu, K. (2016)
This research developed a viable and economical foaming formula (AOS/AVS/N70K-T) which is capable of creating ample and robust CO2 foams. Its foaming ability and displacement performance in a porous medium were investigated and compared with the two conventional formulations (AOS alone and AOS/HPAM). The results showed that the proposed formula could significantly improve the foam stability without greatly affecting the foaming ability, with a salinity level of 20,000 ppm and a temperature of 323 K. Furthermore, AOS/AVS/N70K-T foams exhibited thickening advantages over the other formulations, especially where the foam quality was located around the transition zone. This novel formulation also showed remarkable blocking ability in the resistance factor (RF) test, which was attributed to the pronounced synergy between AVS and N70K-T. Last but not the least, it was found that the tertiary oil recovery of the CO2 foams induced by AOS/AVS/N70K-T was 12.5% higher than that of AOS foams and 6.8% higher than that of AOS/HPAM foams at 323 K and 1500 psi, thus indicating its huge enhanced oil recovery (EOR) potential. Through systematic research, it is felt that the novel foaming formulation might be considered as a promising and practical candidate for CO2 foam flooding in the future.